True mission : socialists and the Labor Party question in the U.S. - Chester, Eric Thomas (Pluto Press, 2004)
In the election campaign of 2000, Al Gore and Ralph Nader polled many millions more votes than George W. Bush. Yet the US Left lost out, a casualty of the two-party system. This is a pattern which has been repeated many times over the years. The most contentious issues dividing the Left in the United States have been those related to the Democratic Party. This book explores the crucial moments in US history where the stranglehold of the two-party system was nearly broken. Presenting a detailed history of Labor party politics, beginning with Henry George's campaign for mayor of New York City in 1886, proceeding to Robert La Follette's independent presidential campaign of 1924, and the Socialist party's relationship to New York's American Labor Party in the early twentieth century, Eric Chester explores the history of Left in America up to and including the Nader campaign of 2000. Chester identifies key reasons why burgeoning political movements have failed. He examines the part played by trade union-based political parties. He also looks at the inabililty of populist middle-class parties to establish ideological or organisational groundings for a viable third party. Looking to the future, Chester proposes an alternative: drawing on the success of the Socialist Party at the turn of the last century, he lays out ideas for a mass-based socialist party as the only way forward towards genuinely independent politics.